How Important is the Environment to Adolescents Today? An Empirical Study on Environmental Awareness among Pupils of Different Age Groups - Zecha, Stefanie (Journal of Geography Education, 2011)
This empirical study investigates the environmental consciousness among pupils aged 14/15 and 18/19 in Bavaria (Southern Germany) by using a questionnaire. The study focuses on the differences between the two samples. Environmental knowledge, attitude and behaviour are important aspects. The author also examines the influence of social and demographic factors – such as gender and the size of the place of residence – on these three aspects. The results show that pupils at the age of 18/19 always have significantly higher scores concerning their environmental knowledge, attitude and behaviour. How nature is experienced as well as attitudes towards the environment within the family are very important factors which affect the various aspects of environmental awareness. The survey finishes with a series of proposals for further investigation and practice.